Usability of Cedrus atlantica in monitoring changes and reducing airborne palladium pollution - Gullizar OZYURT; Halil Baris OZEL; Hakan SEVIK (GSC Online Press, 2024)
Heavy metal pollution has become a global problem threatening the health of humans and other living things. It is crucial to monitor the changes in air concentrations and reduce pollution, mainly due to the potential harm of heavy metals taken into the body by inhalation. For these purposes, plants have begun to be used extensively as biomonitors or accumulators. However, since each heavy metal accumulates in different plants at different levels, the appropriate biomonitor or accumulator species for each heavy metal must be determined separately. This study aimed to assess the usability of Cedrus atlantica, grown in Düzce, where heavy metal pollution is at high levels, for monitoring and reducing the change in palladium (Pd) pollution in the air. Within the scope of the study, changes in Pd concentration in Cedrus atlantica stem sections grown in Düzce, which is among the five most polluted cities in Europe, depending on organ, direction, and age range in the last 60 years, were evaluated. As a result, it was determined that Pd pollution in the region has increased significantly in recent years, and traffic density is thought to be effective in this increase. It was also determined that Cedrus atlantica is a highly suitable species for monitoring the changes in Pd pollution and reducing pollution.
Keywords: Heavy metal; Pollutio; Cedrus atlantica; Palladium; 13. Climate action; 15. Life on land; 6. Clean water